Patent medicine dealers and irrational use of medicines in children: the economic cost and implications for reducing childhood mortality in southeast Nigeria. - Benjamin S C Uzochukwu (Public Library of Science (PLoS), 2014)
This study assessed the economic costs of irrational medicine use by Patent Medicine Dealers (PMDs) for malaria, acute respiratory infection (ARI) and diarrhea diseases (DD) in Nigeria. Exit interviews were conducted with 395 respondents who sought care for their children from 15 PMDs in Abakpa district of Enugu state Nigeria. Of the total respondents, 80.0% received treatment for malaria while 12.0% and 8.0% received treatment for DD and ARI respectively. The average number of drugs dispensed per patient was 6.8, average percentage of patients given injections was 72.5%, average percentage of patients given one or more antibiotics was 59.7%, while the percentage of patients given non essential drugs was 45.9%. The additional costs to the standard treatment in Naira was 255, 350 and 175 for malaria, ARI and DD respectively. The losses attributable to irrational dispensing was 4,500 Naira. However, more than half of the drugs were on essential drug list, implying some cost savings for the consumers, but the high number of drugs (6.8) on average/patient is likely to increase the total cost of drugs cancelling out the cost savings to consumers arising from dispensing essential drugs.